2019
DOI: 10.1177/1079063219839498
|View full text |Cite
|
Sign up to set email alerts
|

Would God Forgive? Public Attitudes Toward Sex Offenders in Places of Worship

Abstract: Previous research has explored the impact of faith and religion on recidivism. However, it focused primarily on violent offenders, drug users, tax evaders, and so on. Missing is an examination of registered sex offenders (RSOs) and the role religion and religiosity play in facilitating reentry. Religiosity and religious organizations may play a role in increasing social bonds and reducing isolation in RSOs. In addition, being surrounded by a faith-based community could act as a catalyst for identity transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…To understand public attitudes towards sexual assault during the #MeToo movement, I conducted a randomized experiment in January 2019 using an online SurveyMonkey audience panel (N = 1,067). The SurveyMonkey audience panel is a type of web-based opt-in survey, which has been frequently used by criminologists to study public opinion about sexual assault (e.g., Dum et al, 2017Dum et al, , 2019Socia et al, 2019a). Compared to nationally representative samples obtained using other methods such as the random digit dialing approach, online opt-in samples may produce data of the same or even higher quality, and are less likely to be influenced by social desirability bias (Chang & Krosnick, 2009;Weinberg et al, 2014).…”
Section: Datamentioning
confidence: 99%
“…To understand public attitudes towards sexual assault during the #MeToo movement, I conducted a randomized experiment in January 2019 using an online SurveyMonkey audience panel (N = 1,067). The SurveyMonkey audience panel is a type of web-based opt-in survey, which has been frequently used by criminologists to study public opinion about sexual assault (e.g., Dum et al, 2017Dum et al, , 2019Socia et al, 2019a). Compared to nationally representative samples obtained using other methods such as the random digit dialing approach, online opt-in samples may produce data of the same or even higher quality, and are less likely to be influenced by social desirability bias (Chang & Krosnick, 2009;Weinberg et al, 2014).…”
Section: Datamentioning
confidence: 99%
“…(Service User 2019, p. 145). The first study to examine attitudes of community members regarding the extent to which persons who have been convicted of sexually offending should be restricted within their faith communities found that acceptance is influenced by different demographic and religious factors (Dum et al 2020). For instance, Dum et al (2020) found that restrictive policies toward inclusion of persons who had sexually offended were endorsed to a greater extent by those with a stronger faith, and by those who held the belief that morality is individualistic rather than originating from God.…”
Section: Interpersonal Strugglesmentioning
confidence: 99%
“…The first study to examine attitudes of community members regarding the extent to which persons who have been convicted of sexually offending should be restricted within their faith communities found that acceptance is influenced by different demographic and religious factors (Dum et al 2020). For instance, Dum et al (2020) found that restrictive policies toward inclusion of persons who had sexually offended were endorsed to a greater extent by those with a stronger faith, and by those who held the belief that morality is individualistic rather than originating from God. Thus, both formal and informal barriers can leave individuals feeling further isolated and rejected instead of experiencing the benefits others in faith communities often receive, such as kindness, compassion, forgiveness, acceptance, and a sense of belonging.…”
Section: Interpersonal Strugglesmentioning
confidence: 99%
See 2 more Smart Citations